„Wieczni prezydenci” są do pokonania. Spostrzeżenia po wyborach samorządowych 2014 roku - Drzonek, Maciej (Studia Politicae Universitatis Silesiensis, 2018)
Abstract: Multi‑terms mayors can be defeated. Observations after the 2014 local government elections From 2002 the mayors of towns in Poland are elected in direct elections every 4 years. In 30 towns with county rights the same persons were chosen in the years 2002—2010. They are so called “everlasting mayors” (multi‑term mayors, incumbents). Before 2014 local elections three of them resigned from the election campaign for re‑election and ten “everlasting mayors” lost the elections. Therefore in thirteen towns with county rights the residents chose new mayors. On the basis of these cases the consideration of some thesis were done. First — the defeated incumbent supported by political parties usually loses elections with nonpartisan candidate; second — the defeated nonpartisan incumbent loses elections with partisan rival. Key words: local politics, the mayor of town’ elections, multi‑term mayors, local power